Innovation of Islamic Education System in Pondok Boarding - Robingun Suyud El Syam; Sri Haryanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is a library research with a qualitative approach. Primary data sources take the relevant laws and regulations and then analyze them with support from secondary sources. The research concludes that Islamic education innovation is a new idea, method or idea for a person or society, either in the form of an invention or a discovery made to achieve the goals of developing Islamic education. The educational innovations found in Islamic Boarding Schools are in the form of organizing diniyah education which is integrated with formal education, at the level of early childhood education, basic education, secondary education, and/or higher education, and mua'is education (equalization). In addition, at Islamic boarding schools there is also a transformation and improvement of the education system which includes teaching methods, curriculum, strengthening soft and hard skills, and applying appropriate technology.